Study into properties of the resourcesaving chromiumcontaining briquetted alloying additive from ore raw materials - Hryhoriev, Stanislav; Petryshchev, Artem; Shyshkanova, Ganna; Yakimtsov, Yurii; Zhuravel, Sergiy; Yamshinskij, Mykhail; Fedorov, Grigoriy; Kruglyak, Dmytro; Shevchenko, Oleksii; Goliev, Yevgen (Eastern-European Journal of Enterprise Technologies, 2017)
It was determined that the original oxide chromium-containing ore raw material is represented by granules of rounded shape the size of 250–600 µm. Along with Cr and Fe, it revealed Mg, Al, Si, Ca, and Ti. They probably were included in the composition of oxide ore impurities and can exert an indirect influence on the reducing processes. Phase composition of the briquetted raw material after the carbon thermal treatment consisted mainly of Cr2O3 and metal Cr with the presence of carbides Cr7C3 and Cr2C3. Diffraction maxima of metal Fe and its compounds had no explicit manifestation, indicating the presence of Fe as substitution atoms in the chromium-containing phases and compounds. The structure is heterogeneous. The content of residual oxygen confirms the presence, along with metal Cr, under-reduced oxide or oxy-carbide compounds. The residual oxygen could also be contained in the composition of oxide related ore impurities. This is confirmed by detection of the specified elements in the examined areas in the images of the microstructure. Excessive carbon content ensures the post-reduction of residual oxide component in a liquid metal in the process of alloying and enables protection against secondary oxidation of chromium